Nursing Care for the Elderly in Meeting the Needs of Skin Integration in Patients with Diabetic Ulcers in 2023 - Fau, Pius Kosmas (Journal of Midwifery and Nursing, 2025)
Diabetic ulcers are a chronic complication of diabetes mellitus that often occurs in the elderly, characterized by open wounds on the skin due to impaired blood circulation and peripheral neuropathy. This condition can disrupt skin integrity, increase the risk of infection, and worsen the patient's quality of life. Nursing care plays a crucial role in meeting skin integrity needs, including assessment, nursing diagnosis, planning, implementation, and evaluation. This study or case report aims to describe the nursing care process for elderly patients with diabetic ulcers based on the nursing process approach. The method used is a case study with data collection techniques through interviews, observation, physical examination, and documentation studies. The results of nursing care indicate that the main problems encountered are impaired skin integrity related to diabetic ulcers, the risk of infection, and acute pain. Interventions provided include standard wound care, self-care education, blood sugar monitoring, and prevention of further complications. Evaluation shows an improvement in wound condition, a decrease in pain complaints, and an increase in patient and family knowledge in ulcer care. Comprehensive nursing care has been proven to help improve the fulfillment of skin integrity needs and the quality of life of elderly patients with diabetic ulcers